Hematological Changes in Dogs Affected with Canine Babesiosis - Bilwal, A.K.; Mandali , G.C.; Patel , A.C. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Canine babesiosis caused by tick-borne organisms of the genus Babesia, is one of the most significant disease worldwide. The aim of this study was to determine the haematological changes in dogs naturally infected with Babesia. The hematological evaluation included haemoglobin (Hb), red blood cell (RBC) count, platelets, white blood cell (WBC) count, differential leucocyte count (DLC), packet cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC). The haematological findings in most of these dogs revealed microcytic hypochromic anaemia, lowered platelet count and 75% cases had 24% decreased PCV. The results of the study showed that Babesia infection in dogs caused anaemia and thrombocytopenia.
Keywords: Dogs; Babesiosis; Hematology; Changes; Anemia